ChemInform Abstract: Copper‐Catalyzed trans‐Carbohalogenation of Terminal Alkynes with Functionalized Tertiary Alkyl Halides. Issue 31 (August 2015) - Che, Chao; Zheng, Hanliang; Zhu, Gangguo
Abstract The presented protocol furnishes alkenyl halides with excellent regioselectivities and trans‐stereoselectivities.